Uji Efektifvitas Cendawan Mikoriza Lokal Gerogak Lahan Kering dan Komersial Pada Tanaman Jagung (Zea mays L.) - Julianus Jeksen (Agriculture Faculty of Flores University, 2012)
Dryland in Indonesia has been dominated by acid soils, so that availability of phosphate (P) becomes the main obstacle in improving outcomes and only 10-30% of fertilizer P can be utilized by plants. One of the solution to meet the needs of phosphate is by utilization of mycorrhizal biofertilizer. These experiments were divided into several phases: 1) Looking for phases of mycorrhizal, 2) the laboratory analysis, 3) Testing phase on plants that were carried out by using polybags with sterile soil. The experiment was designed with a complete randomized block design (RAKL) by using a factor that consists of 6 treatments that are: 1) Without mycorrhizal inoculum (M0), 2) Mycorrhizal inoculum 5 g + 50 Spores (M5), 3) Mycorrhizal inoculum 10 g + 50 spores (M10), 4) Mycorrhizal inoculum 15 g + 50 spores (M15), 5) Mycorrhizal inoculum 20 g + 50 spores (M20), 6) Commercial mycorrhizal 10 g (Mk). All treatments were repeated four times so that the total 24 pot experiment. The experiment results show that mycorrhizal treatment given on the corn crop has very significant (P <0.01) to the number of leaf age of 35, 49, 63 days after, leaf wide have age 49 days after plant, fresh weight, oven-dry weight, absorb P, number of spores, mycorrhizal infection and significant effect (P <0.05) to plant height age of 35, 49, 63 day after plant, 63 days after plant, leaf wide, and P-available. Based on the results of this study will be suggested, in order to enhance the growth of corn plants can be used locally mikroiza a dose of 10 g + 50 spores.